Adjuvant Hepatic Arterial Infusion Chemotherapy Versus Transarterial Chemoembolization for Preventing Early Recurrence After Surgical Resection in Hepatocellular Carcinoma - Xia Y; Wen W; Liao Y; Cai Y; Wan R (Journal of Hepatocellular Carcinoma)
Yangshuo Xia,1,* Wu Wen,1,* Yangyu Liao,2,* Yingxiao Cai,1 Renhua Wan1 1Department of Hepatobiliary Surgery, Nanchang University’s First Affiliated Hospital, Nanchang, Jiangxi, People’s Republic of China; 2Department of Oncology, Nanchang University’s First Affiliated Hospital, Nanchang, Jiangxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Renhua Wan, Department of Hepatobiliary Surgery, Nanchang University’s First Affiliated Hospital, Nanchang, Jiangxi, China, No. 17 Yongwaizheng Street, Donghu District, Nanchang, People’s Republic of China, Email zww726696@sina.comPurpose: HCC exhibits a high postoperative recurrence rate, with early recurrence (≤ 2 years) accounting for 70% of cases, predominantly associated with high-risk recurrence factors. Common adjuvant therapies for HCC include postoperative adjuvant hepatic arterial infusion chemotherapy (PA-HAIC) and postoperative adjuvant transarterial chemoembolization (PA-TACE). This study evaluates the comparative efficacy and safety of PA-HAIC versus PA-TACE in preventing early recurrence among HCC patients with postoperative high-risk recurrence factors.Patients and Methods: A retrospective analysis included 170 HCC patients with high-risk recurrence factors following surgical resection (2018– 2023), divided into PA-HAIC (n=23) and PA-TACE (n=147) groups. To mitigate potential biases and adjust for baseline characteristics, propensity score matching (PSM) was performed. Survival analyses for two primary endpoints, recurrence-free survival (RFS) and overall survival (OS), were then conducted using the Kaplan-Meier method and Cox proportional hazards regression. Adverse event (AE) rates and severity were compared.Results: Post-PSM analysis revealed significantly superior RFS rates in the PA-HAIC group versus PA-TACE at 6,12,and 24 months (100%, 95.7%, 95.7% vs 91.3%, 73.9%, 65.2%;p=0.0085). Multivariable Cox regression identified PA-HAIC (HR=0.20, 95% CI:0.02– 0.71;p=0.020) and intact tumor capsule (HR=0.02, 95% CI:0.00– 0.41;p=0.011) as independent protective factors for RFS, while vascular tumor thrombus (HR=28.02, 95% CI:2.07– 378.81;p=0.012) emerged as a risk factor. Subgroup analyses identified age ≥ 50 years, solitary tumors, BCLC-A stage, absence of MVI, intact capsule, and no vascular thrombus as low-risk factors for early recurrence. Safety profiles showed no significant between-group differences in AE incidence or severity.Conclusion: Among HCC patients with high-risk recurrence factors after surgical resection, PA-HAIC demonstrated significantly prolonged RFS compared to PA-TACE, with a favorable safety profile.Keywords: hepatocellular carcinoma, adjuvant therapy, hepatic arterial infusion chemotherapy, propensity score-matched, transarterial chemoembolization